2011
DOI: 10.1186/1743-422x-8-297
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of enterovirus infection in Chungnam Korea, 2008 and 2009

Abstract: Previously, we explored the epidemic pattern and molecular characterization of enteroviruses isolated in Chungnam, Korea from 2005 to 2006. The present study extended these observations to 2008 and 2009. In this study, enteroviruses showed similar seasonal prevalent pattern from summer to fall and age distribution to previous investigation. The most prevalent month was July: 42.9% in 2008 and 31.9% in 2009. The highest rate of enterovirus-positive samples occurred in children < 1-year-old-age. Enterovirus-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 31 publications
10
50
0
Order By: Relevance
“…Based on complete sequences of VP1genes, sequences of global E30 isolates can be divided into four genetic lineages (A-D) that exhibit at least 15% diversity between clusters. 18 Phylogenetic analysis revealed that the isolate in the described outbreak belonged to the D2 sublineage. An evolutionary tree indicates that E30 isolated in China in recent years belongs to the C group or the D group.…”
Section: Discussionmentioning
confidence: 92%
“…Based on complete sequences of VP1genes, sequences of global E30 isolates can be divided into four genetic lineages (A-D) that exhibit at least 15% diversity between clusters. 18 Phylogenetic analysis revealed that the isolate in the described outbreak belonged to the D2 sublineage. An evolutionary tree indicates that E30 isolated in China in recent years belongs to the C group or the D group.…”
Section: Discussionmentioning
confidence: 92%
“…37 Five genotypes (A-E) were assigned by phylogenetic analyses to coxsackieviruses CV-B3 and CV-B5. 24,124 All Chinese CV-B3 isolates segregated into genotype E but the presence of 2 divergent circulating genotype E strains in Shijiazhuang City (2010-2012) suggests the existence of 2 different lineages. Chinese CV-B3 strains clustered into a genogroup totally different from CV-B3 isolates from other countries.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…EV71 infections are common in children and are acquired largely in the (pre)school years, while spread of these viruses is lower in the other age groups [21]. Echovirus 11 (species human EV-B) is among the most frequently isolated EV serotypes worldwide, while coxsackievirus A strains, including A4, have been implicated in important epidemics around the world [22]. A recent investigation of EV circulation in children identified strains of EV-B and EV-A.…”
Section: Figmentioning
confidence: 99%